Portuguese SMEs: Strategies for collaborative R&D and participation in the framework programme - Abreu, R.; Antunes, J.; Escada, M.; Pádua, M.; Patrício, M. T. (Proceedings of the 18th European Conference on Innovation and Entrepreneurship (ECIE 2023), 2023)
The European Union Framework Programme can create and/or strengthen research networks and cooperation, namely between SMEs and higher education institutions. However, in Portugal, SMEs represent only 16,7% of allocated funds, falling below the European Commission’s target (Agência Nacional de Inovação, 2020). Low SME participation can result from factors particularly related to SMEs, such as organizational characteristics and past R&D experience. In fact, previous collaborative R&D experience is an important factor determining participation in Framework Programmes (Barajas & Huergo, 2010), suggesting a virtuous cycle. How and why do SME gain collaborative experience with HEI? In what kind of collaborative experiences with HEIs do SMEs engage? What are the characteristics of SMEs that engage in these experiences? What obstacles and risks do SMEs face when applying for the FP and which strategies do they adopt to face them? To answer these questions, we conducted an exploratory survey with SMEs that collaborate with HEIs (N = 26). Additionally, we conducted semi-structured interviews with three H2020 participant SMEs and three non-participants to further explore their collaborative practices and R&D strategies.